Anonymous Power Parties, Interest Groups and Politics of Decision Making in Nigeria's Fourth Republic (Essays in Honour of Elochukwu Amucheazi) - Ibeanu, Okechukwu; Okoye, Israel 'Kelue.; Alumona, Ikenna Mike.; Aniche, Ernest Toochi (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2022)
This book examines the structures and processes of political decision-making and governance in Nigeria. Since Nigeria returned to elected government in 1999, it has been observed that several factors account for the differences between the design of statutory structures and processes of political decision-making and how they operate in reality. In other words, there are wide gaps between statutes and practice of political decision-making. However, the nexus between the two remains largely understudied by political scientists. Instinctively, political scientists assume that informal influences in political decision-making are aberrations, episodic or temporary. This book is designed to interrogate the nexus between the formal and non-formal dimensions of the dynamics of political decision making in Nigeria and also provide evidence about the actual functioning of governmental structures in Nigeria. The thesis of the book is that the non-formal dimension of political decision making as evidenced in rising ethno-political patronages, religious sentiments, clientelism and factionalism, are interacting with formal decision-making structures in ways that largely undermine the latter and, by extension, the democratic system. The book pursues this thesis by examining the roles of actors and institutions including, electoral choices made by voters, legislations, which perhaps is the most fundamental form of political decision-making, policies made by the executive and administration, as well as decision making within political parties, since parties are sites for articulating and aggregating issues on which decisions are to be made. Okechukwu Ibeanu is a Professor of Political Science at the University of Nigeria, Nsukka. Israel 'Kelue Okoye is a Professor of Political Science and the Bishop of the Diocese of Ihiala (Anglican Communion). Ikenna Mike Alumona is a Professor of Political Science at Chukwuemeka Odumegwu Ojukwu University, Igbariam, Anambra State, Nigeria. Ernest Toochi Aniche is currently a Senior Lecturer in the Department of Political Science, Federal University Otuoke, Bayelsa State, Nigeria.
Chapter 1: Introduction: The Theory and Practice of Political Decision Making in Nigeria -- Chapter 2: Political Parties, Interest Groups and Governance in Nigeria: Recent Insights -- Chapter 3: Democracy without Demos: Political Mobilization, Public Opinion and Governance in Nigeria -- Chapter 4: Democratic Decay or Democratic Autocracy? Party Primaries and the Challenges of Democratic Consolidation in Nigeria -- Chapter 5: The Powerless Half: Women and Political Decision-making in Nigeria -- Chapter 6: Ethno-Political Organizations and Democracy in Nigeria -- Chapter 7: Union Power: The Quest for Political Power by the Labor Movement -- Chapter 8: Who got what and why? The Politics of Political appointments in Nigeria's fourth republic -- Chapter 9: Power without Responsibility: The Role of Lobbies in Nigerian Democracy -- Chapter 10: From Arbiter to Activist: The Role of the Judiciary in Nigerian Elections -- Chapter 11: Servant or Master: The Civil Service and Governance in Nigeria -- Chapter 12: Zero Sum Politics: Ruling Parties and Political Opposition in Nigeria -- Chapter 13: The State and Party Politics in Nigeria's Fourth Republic -- Chapter 14: The Dialectics of Political Godfatherism in Nigeria, 1999-2019 -- Chapter 15: Godfather Politics in Nigeria: Interrogating the link between Godfatherism and Electoral Violence in Rivers State 2011 -2019 -- Chapter 16: Legislature and Challenges of Law Making in Nigeria -- Chapter 17: Politics of Regime Survival in Nigeria's Fourth Republic (1999-2019) -- Chapter 18: Intra-Party Chicanery and Electoral Outcomes in Nigeria's Presidential Elections -- Chapter 19: Political Contests Beyond the Political Arena: The Dynamics and Challenges of Election Management and Consolidation in Nigeria -- Chapter 20: Conclusion: The Limits of Formal and Informal Power in Nigeria.
Keywords: Africa-Politics and government; Elections; Political science; Political leadership; Executive power; African Politics; Electoral Politics; Governance and Government; Political Science; Political Leadership; Executive Politics